Analisis Karakteristik dan Penilaian Tingkat Kekumuhan Kawasan Permukiman ‘Kampung Braga’ - Kota Bandung - Ake Wihadanto; Baba Barus; Noer Azam Achsani; Deddy S. Bratakusumah (P4W LPPM IPB, 2017)
An unexpected growth of slum settlement has been happening in most of Indonesian cities. “Kampung Braga” is one of the slum areas located in one of strategic areas in the centre of Bandung city. It is an enclave that lies along the side of Cikapundung river and surrounded by the tourism area. This research analyzed characteristics and untidiness level of “Kampung Braga”. The untidiness level assessment was based on dimensions (aspects) stated by Minister of Public Works and Housing’s Regulation no. 02/PRT/M/2016 regarding housing and slum area quality development: (1) building; (2) surrounding road; (3) water; (4) drainage; (5) waste management; (6) trash management; and (7) fire security. This research also formulated composite index that can be used in area quality assessment. The index consists of the following aspects or indicators: (1) The buildings’ density; (2) people’s density per lot; (3) availability of infrastructures and utilities; (4) availability of open public space; (5) inexpediency to area’s spatial planning; and (6) lot’s ownership. The index was determined or calculated based on weighted average of those indicators. The results show that(1) most of the residents are small (low scale) entrepreneurs in trading, with low level of education and income; (2)most of the buildings are under 45 m2, occupied by 8 people (mostly consists of 2 households), lie on high density location, and in improper condition; (3) Low level infrastructures (road, water, waste treatment facility, drainage, and green area); and (4)spatially, the buildings lie irrelarly, and some of those are also located at the bank of Cikapundung river. The overall condition is also reflected in the result of the quantitative assessment that the quality of “Kampung Braga” is categorized as “Very Low” which score of 0.25 (0.00 – 1.00 scale), and “Very High Slum” (score 88). Therefore, “Kampung Braga” needs to be transformed in order to enhance quality of the area, as well as people’s quality of life.